(untitled) (Revista Contexto & Educação, 2023)
The textbook is often the only reference for the work of educators, assuming a central role in the definition of teaching strategies. In addition to interfering in the pedagogical organization of schools, they have a bearing on the culture of citizens, for influencing the values ​​of societies, the way facts present themselves and the process of knowledge transmission itself. Due to its frequent use in school institutions, it is necessary to find out how and in what way gender and sexuality issues are addressed in textbooks. In addition, we try to identify if the books in circulation are free from prejudice and stereotyping. For this, the methodology used was that of ATD (Discursive Textual Analysis). The textbooks examined were from the 8th year of Elementary School, from a school in the southwest of the State of Paraná. It is possible to argue that some of the books analyzed fail to address gender and sexuality cross-cutting issues and that they still contain misleading and outdated information, with a heteronormative view predominating.